1998
DOI: 10.1002/sca.1998.4950200708
|View full text |Cite
|
Sign up to set email alerts
|

Errors in quantitative backscattered electron analysis of bone standardized by energy‐dispersive x‐ray spectrometry

Abstract: Backscattered electron (BSE) imaging has proven to be a useful method for analyzing the mineral distribution in microscopic regions of bone. However, an accepted method of standardization has not been developed, limiting the utility of BSE imaging for truly quantitative analysis. Previous work has suggested that BSE images can be standardized by energy-dispersive x-ray spectrometry (EDX). Unfortunately, EDX-standardized BSE images tend to underestimate the mineral content of bone when compared with traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…Temperature levels at the surface of bone specimens are also positively related to the degree of magnification [58], which in our experiments was kept to low values. Carbon coating prevents charging effects but also reduces the effects of beam damage [59] without compromising the validity of EDX results for calcified tissues [60] provided that it does not contribute to the signal as in the present case with Ca and P measurements. Finally, a larger beam spot size for a given energy can be achieved by increasing the working distance.…”
Section: Electron Beam Damagementioning
confidence: 86%
“…Temperature levels at the surface of bone specimens are also positively related to the degree of magnification [58], which in our experiments was kept to low values. Carbon coating prevents charging effects but also reduces the effects of beam damage [59] without compromising the validity of EDX results for calcified tissues [60] provided that it does not contribute to the signal as in the present case with Ca and P measurements. Finally, a larger beam spot size for a given energy can be achieved by increasing the working distance.…”
Section: Electron Beam Damagementioning
confidence: 86%
“…Although this method has been employed extensively to relate grey levels to calcium content of bone tissue (Vajda, 1996;Misof et al, 2003;Gupta et al, 2005;Sutton-Smith et al, 2008;Busse et al, 2009;Seitz et al, 2010), Monte Carlo simulations of electron trajectories have shown that the 3D x-ray production volume for calcium greatly exceeds the excitation volume of backscattered electrons (Howell and Boyde, 2003). Furthermore, there is evidence that EDX-standardised BSE images tend to give a lower mineral content value of bone than when measured with traditional ash measurements (Vajda et al, 1998). However, an identical approach was used to compare both CON and OVX groups and, as such, these limitations are expected to infl uence each group equally.…”
Section: Discussionmentioning
confidence: 99%
“…As bone mineral content is a determinant of bone strength (Currey, 1984;Ruffoni et al, 2007), alterations in tissue mineral distribution within trabeculae and across anatomical locations might also be indicative of reduced mechanical integrity. Indeed previous computational studies have predicted that increased heterogeneity within trabeculae results in signifi cantly increased stiffness (Van der Linden et al, 2001) and adaptive modelling will likely occur leading to trabecular thinning, bone loss and trabecular perforation (Mulvihill et al, 2008;Van der Linden et al, 2004). Increased heterogeneity between skeletal sites may indicate zones of the bone that are more affected by oestrogen defi ciency and therefore represent weak points.…”
Section: Heterogeneity Of Bone Mineral During Oestrogen Defi Ciencymentioning
confidence: 99%
“…Although BMD is believed to be in close association with the risk of osteoporotic fracture, it is not surprising that in many cases fractures appear partially independent of de- Backscatter electron~BSE! analysis is used for bone analysis~Bloebaum et al ., 1997Vajda et al, 1998! and is the technique in bone research that is most closely related to the one described here.…”
Section: Motivation For the Measurement Of The Elemental Composition mentioning
confidence: 99%